Awareness and knowledge about refractive errors and strabismus in South Indian population - Pallerla, Srinivasa Reddy; Khanna, Rohit C.; Krishnaiah, S.; Keeffe, Jill (International Journal Of Community Medicine And Public Health, 2022)
Background: To assess the awareness, knowledge about refractive errors and strabismus among the general public in southern Indian states of Andhra Pradesh and Telangana. Methods: A cross sectional population-based survey used a semi structured questionnaire on awareness, knowledge on refractive errors and strabismus done as part of knowledge, attitude and practices study (KAP). Stratified multistage cluster random sampling method was used with a sample size of 867 adults- ≥16 years. Having heard of refractive error and strabismus was defined as awareness and having knowledge of the type of error for which spectacles were worn, was considered as knowledge. A pilot study was conducted to validate the questions used in the main study. Statistical package SPSS (version 19) was used for analysis to calculate logistic regression and odds ratios for gender, age, education and urban-rural areas. Results: A total of 782/867 (90.1%) subjects participated in the survey with females 47.4%. 581 subjects (74.3%) were aware of refractive error. 690 subjects (88.2%) were aware of squint. With multiple logistic regression about awareness of refractive error to various variables, subjects who were educated 11th class to degree had a higher awareness (OR: 2.40; CI: 1.25-4.60). With multiple logistic regression about awareness of squint to various variables, females had a higher awareness of squint (OR: 1.98; CI: 1.19-3.31). Conclusions: Awareness of squint and refractive error was high among the general public, but the knowledge of it was limited.